2015
DOI: 10.1007/s00221-015-4396-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial interactions between consecutive manual responses

Abstract: We have shown that the latency to initiate a reaching movement is increased if its direction is the same as a previous movement compared to movements that differ by 90° or 180° (Cowper-Smith and Westwood in Atten Percept Psychophys 75:1914-1922, 2013). An influential study (Taylor and Klein in J Exp Psychol Hum Percept Perform 26:1639-1656, 2000), however, reported the opposite spatial pattern for manual keypress responses: repeated responses on the same side had reduced reaction time compared to responses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Concerning stimulus-response repetition costs, Spadaro et al (2012) have demonstrated their robustness in simple stimulus-identification tasks with intervening response events. Perhaps more importantly still, recent data suggest that stimulus-response repetition costs may be observed in simple stimulus-identification tasks at fixation without intervening response events, as long as the interval between the cue and target is extended beyond the typical CTOA (Ding, He, Satel, & Wang, 2016;Avery, Cowper-Smith, & Westwood, 2015). It thus appears as if, at least in relatively simple two stimulus identification tasks at fixation, some form of inhibition may-eventually-follow from the initial cue representation.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning stimulus-response repetition costs, Spadaro et al (2012) have demonstrated their robustness in simple stimulus-identification tasks with intervening response events. Perhaps more importantly still, recent data suggest that stimulus-response repetition costs may be observed in simple stimulus-identification tasks at fixation without intervening response events, as long as the interval between the cue and target is extended beyond the typical CTOA (Ding, He, Satel, & Wang, 2016;Avery, Cowper-Smith, & Westwood, 2015). It thus appears as if, at least in relatively simple two stimulus identification tasks at fixation, some form of inhibition may-eventually-follow from the initial cue representation.…”
Section: Discussionmentioning
confidence: 99%
“…Various response types have been used to explore the effect, such as manual detection (e.g., Posner & Cohen, 1984;Maylor & Hockey, 1985), manual localization (e.g., Rafal, Egly, & Driver, 1994;Fischer, Pratt, & Neggers, 2003;Avery, Cowper-Smith, & Westwood, 2015), manual discrimination (e.g., Hartley & Kieley, 1995;Lupianez, Milan, Tornay, Madrid, & Tudela, 1997), temporal order judgments (e.g., Posner et al, 1985;Maylor, 1985), and saccadic eye movements (e.g., Vaughan, 1984;Taylor & Klein, 2000;Lim, Eng, Janssen & Satel, 2018).…”
Section: The Model Taskmentioning
confidence: 99%